Preliminary study on the use of hand and handprint for height estimation - Nur Atirah G.; Mardiana S.; Khairulmazidah M. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Formulation of biological profile is one of the important roles of forensic anthropologist. The choice of methods for hand measurement in height estimation studies among researchers are rather static. There are a few methods that have been used by researchers for handprints collection. It ranges from the conventional method of using ink or paint to the use of electronic scanner. It is somehow debatable on which technique provides the most accurate results and depicts the real situation at a crime scene. This preliminary study was conducted to find out the most suitable method of handprint collection and to determine the most suitable time for height measurement. The data obtained were analyzed using Statistical Package for Social Sciences (SPSS) for its general descriptive statistics and their significant differences of mean comparison, in order to determine the most suitable method and time of collection. The result indicated that the most suitable time of collection is between afternoon and evening while for method of collection, it was concluded that any method employed must be consistent throughout the study.